The Status of Professional Business Translators on the Danish Market: A Comparative Study of Company, Agency and Freelance Translators - Dam, Helle; Zethsen, Karen (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article reports on an investigation which forms part of a comprehensive empirical project aimed at investigating the status of professional translators and interpreters in a variety of contexts. The purpose of the research reported on here was to investigate the differences in terms of occupational status between the three groups of professional business translators which we were able to identify in relatively large numbers on the Danish translation market: company, agency and freelance translators. The method involves data from questionnaires completed by a total of 244 translators belonging to one of the three groups. The translators’ perceptions of their occupational status were examined and compared through their responses to questions evolving around four parameters of occupational prestige: (1) salary/income, (2) education/expertise, (3) visibility, and (4) power/influence. Our hypothesis was that company translators would come out at the top of the translator hierarchy, closely followed by agency translators, whereas freelancers would position themselves at the bottom. Although our findings largely confirm the hypothesis and lead to the identification of a number of differences between the three groups of translators in terms of occupational status, the analyses did in fact allow us to identify more similarities than differences. The analyses and results are discussed in detail, and avenues for further research are suggested.